(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
ABSTRACT: The current article analyzes the inextricable and instrumental link between intangible religious heritage and tangible religious heritage. More specifically, UNESCO’s nomination processes are examined in order to investigate the evolution and the approach of national and global institutions to intangible religious heritage. Rituals, architectural techniques of constructions and several UNESCO’s nomination dossiers of religious towns are used to shed a light on problematic aspects. Among them, we should wonder if intangible religious heritage underwent a process of political “instrumentalization”, “scientificization” and “objectivization”: which are the consequences of this institutional activity? SUMMARY: 1. Introduction - 2. Intangible Heritage and Legal Framework - 3. The National Dimension of UNESCO’s Nomination Processes - 4. The Global Dimension of UNESCO’s Nomination Processes - 5. Intangible Religious Heritage and Criticalities: Is There a Political Instrumentality? - 6. Architectural Techniques of Construction: Uncharted Aspects and Legal Issues - 7. Architectural Techniques of Construction and UNESCO - 8. Rituals: Uncharted Aspects and Legal Issues - 9. Rituals and UNESCO - 10. Conclusions.